Perubahan Morfologi Pantai Dengan Integrasi Citra Di Wilayah Kabupaten Bengkulu Utara - Nofirman Nofirman (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2017)
The coastal area has become an area of ​​high and complex dynamics. Changes that occur tend to the beach being built. The coastal ecosystem contains a rich diversity of fauna (biological) and mutually synergic floran.The purpose of this research is to know: (1) shoreline movement with the integration of Landsat image, (2) coastal morphology change with the integration of high-resolution image quality.The location of the research is in North Bengkulu Regency where the determination of the unit of analysis is based on the abscissa, namely; (1) the area along the coast of Cipta Mulya (Putri Hijau), (2) the area along the Air Petai Beach (Putri Hijau), (3) the area along the coast of Urai (Ketahun), (4) the area along the coast of Sengarai (Ketahun), (5) ) area along the shores of the Seaside (Air Napal). Image data used is Landsat Image downloaded from the website earthexplorer.usgs.gov with path 125 and row 63. The image used was acquired in 2000, 2005, 2010, 2015, 2017. Data processing (image) remote sensing is done by step- ; (c) the manufacture of color composites, (d) digitization on screen, (e) overlay analysis, and (f) analysis and displacement of the morphology beach.The research findings from Landsat image data processing in 2000, 2005, 2010, 2015 and 2017 in 5 areas of abscissa indicate different shoreline displacement conditions and for each year of the image. The similarities that occur in the 5 areas of absorption is the occurrence of abrasion and accretion events. Based on the use of image data with a distance of 5 years, there was an unobserved coastline shift to show the abrasion activity that occurred. Changes in coastal morphology occur in bumpy terrain, bumpy hills, terrain, and river estuaries overlooking the sea. The condition of the beach has long been interrupted by abrasion activity, resulting in the coastal morphology of steep cliffs, poles (stack), while on steep cliffs also formed coastal caves, as symptoms of wave erosion or ocean currents.